2018
DOI: 10.1037/men0000122
|View full text |Cite
|
Sign up to set email alerts
|

When do people “check out” male bodies? Appearance-focus increases the objectifying gaze toward men.

Abstract: Abstract:Objectification studies have mostly focused on why and how women are objectified, but relatively little is known about what drives the objectification of men. This paper aims to examine the objectifying gaze toward men, which is operationalized in the present paper as decreased focus on men's faces and increased focus on men's body parts (arms, chest and stomach). We considered the role of appearance (vs. personality) focus and ideal body shape on the objectifying gaze toward men. Specifically, we ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
29
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 18 publications
(37 citation statements)
references
References 34 publications
6
29
2
Order By: Relevance
“…Whereas previous research showed that focusing on people's faces might temper the effects of appearance-focus and sexualization on cognitive objectification (Bernard, Gervais, Holland, & Dodd, 2018;Gervais, Holland, & Dodd, 2013;Nummenmaa, Hietanen, Santtila & Hyönä, 2012) and related dehumanization (Gray et al, 2011;Loughan et al, 2010), our results suggest that such intervention may not be efficient when faces are sexualized, especially through the use of eye makeup (e.g., mascara).…”
Section: Discussioncontrasting
confidence: 97%
“…Whereas previous research showed that focusing on people's faces might temper the effects of appearance-focus and sexualization on cognitive objectification (Bernard, Gervais, Holland, & Dodd, 2018;Gervais, Holland, & Dodd, 2013;Nummenmaa, Hietanen, Santtila & Hyönä, 2012) and related dehumanization (Gray et al, 2011;Loughan et al, 2010), our results suggest that such intervention may not be efficient when faces are sexualized, especially through the use of eye makeup (e.g., mascara).…”
Section: Discussioncontrasting
confidence: 97%
“…However, we did not examine sexual objectification with other sex dyads. Men sexually objectify women daily, but women can also be sexually objectified by women (Loughnan, Pina, Vasquez, & Puvia, 2013; Vaes et al, 2011), and men are sometimes sexually objectified by women and by men (Bernard, Gervais, Holland, & Dodd, 2018). Further research may test the effect of sexual objectification on retaliatory aggression with other sex dyads, such as when men are sexually objectified by men or by women, or women by women, and uncover the corresponding psychological mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Another complementary explanation is that target sexualization disrupts configural processing through an increased focus on sexual body parts. Behavioral research reveals that people fixate longer on sexual body parts and on the face less when looking at sexualized bodies (Nummenmaa et al, 2012) and when asked to focus on men's and women's physical apperance (Bernard, Gervais, Holland, & Dodd, in press; Gervais, Holland, & Dodd, 2013). Studies using functional magnetic resonance imaging (fMRI) also show that face-selective neural networks mediate the body inversion effect (Brandman & Yovel, 2010), explaining why headless bodies are related to a lack of configural processing (Minnebusch et al, 2009).…”
Section: Discussionmentioning
confidence: 99%